Tumor-associated macrophages in bladder cancer: roles and targeted therapeutic strategies - Ma, Yuanchun; Sun, Ying; Guo, Hongqian; Yang, Rong (Frontiers in Immunology, 2024)
Bladder cancer (BC) is the ninth most common and “expensive” cancer in the world. Despite the availability of various treatment modalities such as chemotherapy, immunotherapy and surgery, the overall survival rate of patients with advanced bladder cancer remains low. As one of the most abundant infiltrating immune cells in bladder cancer, tumor-associated macrophages (TAMs) play an important role in the development of BC and in the standard regimen of intravesical BCG therapy. Targeting TAMs have achieved excellent results in clinical trials for a variety of other cancers, but few studies have been conducted for bladder cancer. Further exploration is still needed to develop TAM-related therapeutic strategies for BC treatment, which are expected to improve the therapeutic efficacy and life quality of patients. This review summarizes the relationship between TAMs in bladder cancer and disease staging, evolution, patient prognosis, and treatment outcome. Several potential TAM targets in BC are also pointed, which may help to inhibit tumor-promoting TAMs and provide new therapeutic approaches for advanced BC.